Green Leadership and Sustainable Employee Engagement in Driving Organizational Citizenship Behavior for the Environment (OCBE): A Systematic Literature Review - Supriyatno; Setyo Riyanto; Lenny C. Nawangsari; Agus Arijanto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This article presents a systematic literature review that explores the linkages between green leadership, sustainability-focused employee engagement, and today's organizational context. Using the PRISMA 2020 framework, this study examined 45 peer-reviewed  articles published between 2020 and 2025. The results of this survey reveal that green leadership styles, especially green transformational leadership, environmentally-specific servant leadership (ESSL), and eco-centric leadership have been proven to have a significant effect on employee engagement in various sustainability initiatives and are able to encourage pro-environmental behaviors that are carried out voluntarily. Important findings in this study show that sustainable employee engagement plays a key mediator linking green leadership to OCBE. The mechanisms behind it include green psychological capital (GpsyCap), green organizational climate, and environmental self-efficacy. The study also identified three key dimensions of OCBE, namely eco-initiatives, eco-civic engagement, and eco-assistance, all of which are positively influenced by authentic green leadership. The practice of Green Human Resource Management (GHRM) is also present as a supporting mechanism that strengthens the path of leadership, involvement, OCBE. From a theoretical perspective, this approach contributes by presenting a comprehensive framework that combines various perspectives and into a whole whole. In practical terms, these findings underscore the importance of organizations investing in green leadership competency development, building a well-rounded GHRM system, and creating an organizational climate conducive to employees' voluntary environmental civic behavior.